Voice and Voices in Antiquity : Orality and Literacy in the Ancient World, Vol. 11 - Slater, Niall W. (Mnemosyne, Supplements Ser, 2016)
‎Contents -- ‎Acknowledgements -- ‎Notes on Contributors -- ‎Chapter 1. Introduction (Slater) -- ‎Part 1. Epic Voices -- ‎Chapter 2. Voice and Voices: Homer and the Stewardship of Memory (Minchin) -- ‎Chapter 3. Which Limits for Speech Reporting? Messenger Scenes and Control of Repetition in the Iliad (Cesca) -- ‎Chapter 4. The Voice of the Seer in the Iliad and the Odyssey (Beck) -- ‎Chapter 5. The Individual Voice in Works and Days (Scodel) -- ‎Chapter 6. Nestor's Cup and Its Reception (Gaunt) -- ‎Part 2. Lyric and Dramatic Voices -- ‎Chapter 7. Pindar's Voice(s): The Epinician Persona Reconsidered (Lattmann) -- ‎Chapter 8. Poeta Loquens: Poetic Voices in Pindar's Paean 6 and Horace's Odes 4.6 (Foster) -- ‎Chapter 9. Melizein Pathe or the Tonal Dimension in Aeschylus' Agamemnon: Voice, Song, and Choreia as Leitmotifs and Metatragic Signals for Expressing Suffering (Bierl) -- ‎Chapter 10. Daphnis' Folksong: The Euphonist's Effect on the Creation of a Textual Performance (Kaloudis) -- ‎Part 3. From Singing to Narrative Voice -- ‎Chapter 11. Towards a Grammar of Narrative Voice: From Homeric Pragmatics to Hellenistic Stylistics (Willi) -- ‎Chapter 12. The Voice of Aeschylus in Plato's Republic (Bakewell) -- ‎Chapter 13. Character in Narrative Depictions of Composing Oral Epics and Reading Historiographies (Person) -- ‎Part 4. Voices of Prose -- ‎Chapter 14. Written Record and Membership in Persian Period Judah and Classical Athens (Buster) -- ‎Chapter 15. Voiced Mathematics: Orality and Numeracy (van Berkel) -- ‎Chapter 16. Cicero's Representation of an Oral Community in De Oratore (Kenty) -- ‎Chapter 17. Becoming Gallic: Orality, Voice and Identity in Roman Gaul (Fisher) -- ‎Chapter 18. ‭λόγος‬ and ‭φωνή‬ in Odyssey 10 and Plutarch's Gryllus (Kirk) -- ‎Chapter 19. The Fragrance of the Rose: An Image of the Voice in Achilles Tatius (Koenig).